Vernuwing in die kerklied: die Liedboek van die Kerk (2001) - E. C. Kloppers (Acta Theologica)
Renewal in hymnody and an “explosion” of hymns are taking place world-wide. Many new hymnals were published in the past decades. A new hymnal in Afrikaans, Liedboek van die Kerk, was also taken into use during 2001. In this article certain aspects of renewal reflected in this hymnal are discussed and related to world-wide tendencies. Aspects discussed are liturgical forms and hymns handed down from the early history of the church; forms promoting more active participation; ecumenicity; diversity and plurality to accommodate various groups and generations; the versification of the Psalter; the rubrication; and the formation of liturgists. It is shown which aspects were addressed successfully and which should receive more attention in future.